Feminist postcolonial theory : a reader - Lewis, Reina, 1963-; Mills, Sara, 1954- (Edinburgh : Edinburgh University Press, 2003)
The readings have been selected to examine the textual and discursive nature of colonial and post-colonial discourse in relation to gender and the material effects of the post-colonial condition and practices developed in relation to it.
1 Gendering colonialism and postcolonialism/ Recialialising feminism -- 2 Rethinking whiteness -- 3 Redefining the "Third- World" subject -- 4 Sexuality and sexual rights -- 5 Harem and the veil -- 6 Gender and post/Coloninal spatial relations.
Includes bibliographical references (pages 739-746) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Feminist theory -- History; Feminism -- History; Postcolonialism; Théorie féministe -- Histoire; Féminisme -- Histoire; Postcolonialisme; postcolonialism; SOCIAL SCIENCE -- Feminism & Feminist Theory; Feminism; Feminist theory; Postcolonialism; Feminismus; Postkolonialismus; Feminisme; Postkolonialisme; Theorie; Théorie féministe -- Histoire; Féminisme -- Histoire; Postcolonialisme; Aufsatzsammlung; History